THE CORRELATION BETWEEN READING COMPREHENSION AND WRITING RECOUNT TEXT ABILITY OF THE SECOND YEAR STUDENTS OF SMP YLPI PERHENTIAN MARPOYAN PEKANBARU - Rahmi Saskia Putri; Eliwarti Eliwarti; Syofia Delfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study was to find out the correlation between reading comprehension and ability in writing recount text of the second year students of SMP YLPI Perhentian Marpoyan Pekanbaru. The samples of the research were 46 second year students of SMP YLPI Perhentian Marpoyan Pekanbaru. There were a reading comprehension test consisted of 30 questions about recount text and writing a recount text test as the instruments of this research. The time allocation was 60 minutes for the entire test. The data were obtained by students’ scores of reading comprehension test and writing test. The data for writing test were graded by three raters by using an analytical scoring system. The finding shows that the students had a fair level ability in both reading and writing. To see the correlation between the two variables, the primary data were analysed and correlated by using the Product Pearson Product Moment Correlation on SPSS 26.0 Program. Based on findings, the correlation between students’ reading comprehension (X) and their ability in writing (Y), the correlation coefficient (rxy) was 0.642 and it was categorized as a fair correlation. It could be concluded that there was a significant correlation between reading comprehension and ability in writing. It is suggested for teachers to help students use English verb tenses appropriately, teachers are also expected to clearly show how each tense is formed. It is also suggested that future research could further examine the relationship between other English skills.Key Words: Correlation, Reading Comprehension, Writing Ability, Recount Texts